Color control of nanowire InGaN/GaN light emitting diodes by post-growth treatment. (28th October 2015) - Zhang, Hezhi; Jacopin, Gwénolé; Neplokh, Vladimir; Largeau, Ludovic; Julien, François H; Kryliouk, Olga; Tchernycheva, Maria
Abstract: Core/shell InGaN/GaN nanowire light emitting diodes (LEDs) based on vertically standing single nanowires and nanowire arrays were fabricated and extensively characterized. The emission of single wire LEDs with the same conformal contact geometry as the array device exhibits the same broadening as the array LED electroluminescence, which proves an excellent wire-to-wire homogeneity. The electroluminescence spectra present two peaks corresponding to the m-plane InGaN quantum well (blue emission) and to an In-rich region at the m-plane-semipolar plane junction (green emission), in agreement with structural characterizations. Modification of the contact layout and a post-growth plasma treatment enable strongly suppressing the unwanted green electroluminescence while increasing the intensity in the blue spectral range for the same injected electrical power. Electron beam induced current mapping proves the inhibition of the electrical activity of the top part of the nanowire after plasma treatment. Inductively coupled plasma etching of the In-rich region permits one to completely remove the green emission for all injection currents, but loss of intensity in the blue spectral range is observed. Selectively contacting the m-plane and plasma treatment of the top part of the nanowire appear as a viable solution for controlling the color of core/shell nanowire LEDs with an inhomogeneous indium composition.